2000
DOI: 10.1152/jn.2000.83.5.2996
|View full text |Cite
|
Sign up to set email alerts
|

D1 Dopamine Receptor Activation Reduces GABAA Receptor Currents in Neostriatal Neurons Through a PKA/DARPP-32/PP1 Signaling Cascade

Abstract: Dopamine is a critical determinant of neostriatal function, but its impact on intrastriatal GABAergic signaling is poorly understood. The role of D(1) dopamine receptors in the regulation of postsynaptic GABA(A) receptors was characterized using whole cell voltage-clamp recordings in acutely isolated, rat neostriatal medium spiny neurons. Exogenous application of GABA evoked a rapidly desensitizing current that was blocked by bicuculline. Application of the D(1) dopamine receptor agonist SKF 81297 reduced GABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 48 publications
(66 reference statements)
4
104
0
Order By: Relevance
“…Bicuculline-sensitive currents, evoked intrastriatally, were significantly reduced by the D 1 agonist ( p Ͻ 0.01) (Fig. 7F ) (Flores-Hernández et al, 2000;Gao et al, 2003). In some cases IPSC amplitude did not change, as seen in the time course of Figure 8 D. This is opposite from the findings after antidromic GP stimulation.…”
Section: Probing Dopaminergic Receptor Agonists With the Paired-pulsementioning
confidence: 71%
See 1 more Smart Citation
“…Bicuculline-sensitive currents, evoked intrastriatally, were significantly reduced by the D 1 agonist ( p Ͻ 0.01) (Fig. 7F ) (Flores-Hernández et al, 2000;Gao et al, 2003). In some cases IPSC amplitude did not change, as seen in the time course of Figure 8 D. This is opposite from the findings after antidromic GP stimulation.…”
Section: Probing Dopaminergic Receptor Agonists With the Paired-pulsementioning
confidence: 71%
“…On the other hand, although PPR did not change consistently during D 1 receptor agonists, a significant and consistent decrease in IPSCs amplitude was seen, suggesting a mixture of postsynaptic (Flores-Hernández et al, 2000) and presynaptic (Centonze et al, 2003;Gao et al, 2003) D 1 effects. This latter effect is the opposite of that found on IPSCs from axon collaterals and striatonigral terminals (Radnikow and Misgeld, 1998), demonstrating that the same modulator may have opposite actions on different GABAergic connections and neurons.…”
Section: Ipscs From Axon Collateralsmentioning
confidence: 78%
“…Variance-mean analysis (Fig. 5G) suggested that this action was postsynaptic (53). However, it coursed with a decrease in quantal amplitude (54), implying, perhaps, a mixture of pre-and postsynaptic actions.…”
Section: Modulation Of Synapses Between Fs Interneurons and Spiny Neumentioning
confidence: 92%
“…For these studies, we focused on dopamine D 1 receptors, which have been established previously to modify GABA A receptor function via a PKA-dependent mechanism (Hernandez et al, 2000). First, we examined the effects of D 1 receptor activation on GABA A receptor ␤3 subunit phosphorylation in wild-type and PRIP-1 Ϫ/Ϫ mice.…”
Section: Prip-1 Is Required For Dopamine Receptor Modulation Of Gaba mentioning
confidence: 99%